2019
DOI: 10.3389/fevo.2019.00405
|View full text |Cite
|
Sign up to set email alerts
|

Rearing Success Does Not Improve With Apparent Pair Coordination in Offspring Provisioning

Abstract: In species with biparental care, behavioral coordination in the provisioning of the progeny is hypothesized to increase the number of offspring that survive to independence. Coordination is often quantified by two metrics, alternation and synchrony. Turn-taking (leading to an alternation pattern) can result when one parent's investment strategy is based on the investment of its partner (i.e., conditional cooperation). This should increase the overall provisioning rate and improve offspring body condition. Sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In this respect, we found that suburban pairs fledged lighter chicks. However, it is notoriously difficult to assess the impact of reduced alternation alone on offspring fitness in correlative studies 72,73 , especially in situations in which fledgling weight is also likely to be function of provisioning rate, food availability and habitat composition such as in this study. Experimental manipulations of one parent's investment (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…In this respect, we found that suburban pairs fledged lighter chicks. However, it is notoriously difficult to assess the impact of reduced alternation alone on offspring fitness in correlative studies 72,73 , especially in situations in which fledgling weight is also likely to be function of provisioning rate, food availability and habitat composition such as in this study. Experimental manipulations of one parent's investment (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Mariette and Griffith, 2012). Synchronized, rather than independent nest visits may reduce sibling competition through more equal food distribution between offspring or decrease the chance of depredation as a result of lower number of overall nest visits (Shen et al, 2010;Mariette and Griffith, 2012;Leniowski and Wegrzyn, 2018;Wojczulanis-Jakubas et al, 2018;Ihle et al, 2019). In addition, synchronized provisioning behaviour might be the result of other, nonparental activities, for instance foraging patterns (Masello et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Between 2004 and 2015, videos (N=2112) were manually annotated by postgraduate students and researchers, which contributed to multiple publications (see Ihle et al, 2019;Nakagawa et al, 2007;Schroeder et al, 2019Schroeder et al, , 2016Schroeder et al, , 2013Schroeder et al, , 2012. We used these data as a baseline -the 'manual feed rate' -to be compared against the automatically-collected data ('automatic feed rate') outlined below.…”
Section: Parental Provisioning Videosmentioning
confidence: 99%
“…As such, a large body of literature focuses on how nest visit frequency with dependent young is associated with aspects of an animal's life history, with a focus on birds, where 90% of species engage in parental care (Cockburn, 2006). For example, work on life history trade-off in terms of parent and offspring fitness (Schroeder et al, 2013), parent coordination (see Ihle et al, 2019;Wojczulanis-Jakubas et al, 2018), parent-offspring conflict (Estramil et al, 2013), or ageing (Wilcoxen et al, 2010) all used the frequency of parental visits to nests (or provisioning) as a proxy of parental investment.…”
Section: Introductionmentioning
confidence: 99%